Non-invasive brain stimulation can induce paradoxical facilitation. Are these neuroenhancements transferable and meaningful to security services? - Levasseur-Moreau, Jean; Brunelin, Jerome; Fecteau, Shirley (Frontiers in Human Neuroscience, 2013)
For ages, we have been looking for ways to enhance our physical and cognitive capacities in order to augment our security. One potential way to achieve this goal may be to externally stimulate the brain. Methods of noninvasive brain stimulation (NIBS), such as repetitive transcranial magnetic stimulation and transcranial electrical stimulation, have been recently developed to modulate brain activity. Both techniques are relatively safe and can transiently modify motor and cognitive functions outlasting the stimulation period. The purpose of this paper is to review data suggesting that NIBS can enhance motor and cognitive performance in healthy volunteers. We frame these findings in the context of whether they may serve security purposes. Specifically, we review studies reporting that NIBS induces paradoxical facilitation in motor (precision, speed, strength, acceleration endurance, and execution of daily motor task) and cognitive functions (attention, impulsive behaviour, risk-taking, working memory, planning, and deceptive capacities). Although transferability and meaningfulness of these NIBS-induced paradoxical facilitations into real life situations are not clear yet, NIBS may contribute at improving training of motor and cognitive functions relevant for military, civil and forensic security services. This is an enthusiastic perspective that also calls for fair and open debates on the ethics of using NIBS in healthy individuals to enhance normal functions.